Dose adjustment not required for contezolid in patients with moderate hepatic impairment based on pharmacokinetic/pharmacodynamic analysis - Wu, Junzhen; Yang, Xinyi; Wu, Jufang; Wang, Jingjing; Wu, Hailan; Wang, Yu; Yuan, Hong; Yang, Huahui; Wang, Hailin; Zhang, Jing (Frontiers in Pharmacology, 2023)
Objective: Contezolid is an oxazolidinone antimicrobial agent newly approved for treatment of Gram-positive bacterial infections. It is primarily metabolized by the liver. This study aimed to assess whether it is required to adjust the dose of contezolid in patients with moderate hepatic impairment for clinicians to use the drug more rationally. Methods: A single-center, open-label, parallel-group study was conducted to compare the pharmacokinetic (PK) parameters of contezolid and its metabolite M2 between the patients with moderate hepatic impairment and healthy controls with normal liver function after oral administration of 800 mg contezolid tablets. Monte Carlo simulation was performed to calculate the probability of target attainment (PTA) and cumulative fraction of response (CFR) of contezolid based on the PK and pharmacodynamic data. Results: Oral treatment with 800 mg contezolid tablets was safe and well tolerated in both the patients with moderate hepatic impairment and healthy controls. Moderate hepatic impairment did not result in substantial difference in the area under the concentration-time curve from 0 to 24 h (AUC0-24h, 106.79 vs 97.07 h∙µg/mL) of contezolid even though lower maximum concentration (Cmax, 19.03 vs 34.49 μg/mL) compared with healthy controls. The mean cumulative amount excreted in urine from 0 to 48 h (Ae0-48h) and renal clearance (CLR) of contezolid did not show significant difference between the two groups. Moderate hepatic impairment was associated with lower Cmax, slightly lower AUC and Ae0-48h of M2 compared to the healthy controls. AUC/MIC was the best PK/PD index to predict the clinical efficacy of contezolid. Monte Carlo simulation results indicated that at the proposed AUC/MIC target value of 2.3, the dosing regimen of oral contezolid 800 mg q12h could achieve satisfactory PTA and CFR (both > 90%) for the target pathogen (methicillin-resistant S. aureus, MIC ≤ 4 mg/L) in patients with moderate hepatic impairment. Conclusion: Our preliminary data suggest that dose adjustment is not required for contezolid in patients with moderate hepatic impairment.